The Influence of COVID-19 Pandemic on Physical Health–Psychological Health, Physical Activity, and Overall Well-Being: The Mediating Role of Emotional Regulation - Dai, Jianhui; Sang, Xuehui; Menhas, Rashid; Xu, Xia; Khurshid, Sumaira; Mahmood, Sajid; Weng, Yu; Huang, Jiaai; Cai, Yuwei; Shahzad, Babar; Iqbal, Waseem; Gul, Maryam; et al. (Frontiers in Psychology, 2021)
Background: Highly infectious respiratory disease COVID-19 emerged in Wuhan, China, and spread worldwide. Different measures have been adopted worldwide to contain the COVID-19, and these measures have various impacts on health-related quality of life. This study aimed to assess the impact of the COVID-19 pandemic and lockdown policy on physical-psychological health, physical activity, and overall well-being in the context of health-related quality of life, exploring the mediating role of emotional regulation. Method: The current study was conducted in two provincial cities of China. An online survey was conducted in both cities to collect the data. After quantifying the data, a total of 2200 respondent's data was analyzed through appropriate statistical techniques. Results: The study results indicate COVID-19 pandemic was found significantly and negatively related to physical health (β = -0.157, t=9.444, p< 0.001). Significant relationship was found between Covid-19 pandemic and psychological health (β = 0.779, t = 45.013, p< 0.001). The third prediction revealed a significant negative relationship between the COVID-19 pandemic and overall well-being (β= -0.080, t= 5.261, p < 0.001). The COVID-19 pandemic and physical activity have a significant negative relationship (β= -0.047, t= 3.351, p < 0.001). Conclusion: The Chinese people's physical health, psychological health, and overall well-being were affected due to the COVID-19 pandemic and lockdown measures. It is suggested that emotion regulation intervention reduce the negative psychological impacts for improving quality of life. Emotion regulation can function one's sentiments in their social environment effectively for quality of life.